2017
DOI: 10.1200/jco.2015.65.7916
|View full text |Cite
|
Sign up to set email alerts
|

Role of Troponins I and T and N-Terminal Prohormone of Brain Natriuretic Peptide in Monitoring Cardiac Safety of Patients With Early-Stage Human Epidermal Growth Factor Receptor 2–Positive Breast Cancer Receiving Trastuzumab: A Herceptin Adjuvant Study Cardiac Marker Substudy

Abstract: Purpose Women receiving trastuzumab with chemotherapy are at risk for trastuzumab-related cardiac dysfunction (TRCD). We explored the prognostic value of cardiac markers (troponins I and T, N-terminal prohormone of brain natriuretic peptide [NT-proBNP]) to predict baseline susceptibility to develop TRCD. We examined whether development of cardiac end points or significant left ventricular ejection fraction (LVEF) drop was associated with markers' increases. Patients and Methods Cardiac marker assessments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
119
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 32 publications
7
119
0
Order By: Relevance
“…Radiotherapy and HER2 inhibitor therapy without concomitant chemotherapy had no detectable effect upon troponin levels (OR 3.4, 95% CI 1.0–12.2; n = 810 for HER2 inhibitor therapy; and OR 1.0, 95% CI 0.1–16.4; n = 125 for radiotherapy, respectively). The frequency of troponin elevations in studies that assessed troponin I was similar to the frequency in studies investigating troponin T [OR 12.2 for troponin I vs. OR 8.9 for troponin T; Chi 2 = 0.09; P = 0.77 for subgroup differences; total n = 1863 with three studies ( n = 426) included for both forms of troponin] (online supplementary Figure ). Within anthracycline‐treated patients with or without concomitant HER2 inhibitor therapy, the risk for troponin elevation was similar in patients receiving < 240 and ≥ 240 mg/m 2 doxorubicin equivalent dose (OR 17.2 for < 240 mg/m 2 vs. OR 19.3 for ≥ 240 mg/m 2 doxorubicin equivalent dose; Chi 2 = 0.04; P = 0.84 for subgroup differences; n = 1129) (online supplementary Figure ).…”
Section: Resultsmentioning
confidence: 68%
“…Radiotherapy and HER2 inhibitor therapy without concomitant chemotherapy had no detectable effect upon troponin levels (OR 3.4, 95% CI 1.0–12.2; n = 810 for HER2 inhibitor therapy; and OR 1.0, 95% CI 0.1–16.4; n = 125 for radiotherapy, respectively). The frequency of troponin elevations in studies that assessed troponin I was similar to the frequency in studies investigating troponin T [OR 12.2 for troponin I vs. OR 8.9 for troponin T; Chi 2 = 0.09; P = 0.77 for subgroup differences; total n = 1863 with three studies ( n = 426) included for both forms of troponin] (online supplementary Figure ). Within anthracycline‐treated patients with or without concomitant HER2 inhibitor therapy, the risk for troponin elevation was similar in patients receiving < 240 and ≥ 240 mg/m 2 doxorubicin equivalent dose (OR 17.2 for < 240 mg/m 2 vs. OR 19.3 for ≥ 240 mg/m 2 doxorubicin equivalent dose; Chi 2 = 0.04; P = 0.84 for subgroup differences; n = 1129) (online supplementary Figure ).…”
Section: Resultsmentioning
confidence: 68%
“…The primary outcome measure of CTRCD was a priori defined as a reduction in LVEF by ≥10% from baseline prior to chemotherapy, to an absolute value of <50%. Although there is no universally accepted definition of CTRCD, this definition has been commonly used in the cardio-oncology literature (2224). …”
Section: Methodsmentioning
confidence: 99%
“…Cardiac troponins are well‐established markers of myocardial injury and appear to correlate best with incident cardiac dysfunction following chemotherapy. Three studies have reported that elevated and increasing troponin I following chemotherapy, particularly if such increase persists at 1 month after treatment,84 is associated with subsequent cardiac dysfunction as well as with lower likelihood of cardiac recovery in patients receiving trastuzumab 85, 86, 87. During treatment, negative cardiac troponin has a high negative predictive value; however, minute elevations can be commonly detected in patients following chemotherapy and have low positive predictive value 88.…”
Section: Monitoring For Cardiac Dysfunction During Her2‐targeted Therapymentioning
confidence: 99%